Exclusivism: Religious Constructs in Tafsir Muhammad Bin Salih Al-'Uthaimin - Zaenal Khalid; Yusuf Rahman; Sabo Jamilu Saidu (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
Abstract: This paper analyzes the exclusive paradigm in the interpretation of Muhammad bin Sa>lih al-‘Uthaimi>n. The methodology used is qualitative descriptive-analytical to describe how the exclusive paradigm of Muhammad bin Sa>lih al-‘Uthaimi>n on his interpretation and implications for his religious concept. This paper uses semantic-linguistic, theological, and sociological approaches. This research found that exclusivism in the interpretation of Muhammad bin Salih al- ‘Uthaimin was built by the textualist-literal interpretation paradigm which is supported by romanticism towards the orthodoxy of traditional interpretation so that it has implications for the conception of religion which exclusively views Islam as one only true religion (truth claim), which can guarantee salvation (salvation claim). Keywords: exclusivism, textualist, truth claim.